Human rights and the criminal justice system - Amatrudo, Anthony; Blake, Leslie William (Milton Park, Abingdon, Oxon : Routledge, 2015)
'Human Rights and the Criminal Justice System is an advanced text that addresses the conjunction of these two areas. We now live in a world which thinks through the legislative implications of criminal justice with one eye on human rights. This book brings together the relevant legal and the criminological material in order to critically review the relationship between the developing body of human rights theory and practice, and the criminal justice system. Taking up a thorough analysis of this relationship, Human Rights and the Criminal Justice System examines existing legal structures, court practices, and the developing literature in criminology, law and political science. It will be of considerable interest to those with academic concerns in this area; as well as providing an accessible, yet sophisticated, resource for relevant upper level undergraduate and postgraduate courses.'--
'We now live in a world which thinks through the legislative implications of criminal justice with one eye on human rights. Human Rights and the Criminal Justice System provides comprehensive coverage of human rights as it relates to the contemporary criminal justice system. As well as being a significant aspect of international governance and global justice, Amatrudo and Blake argue here that human rights have also eclipsed the rhetoric of religion in contemporary moral discussion. This book explores topics such as terrorism, race, and the rights of prisoners, as well as existing legal structures, court practices, and the developing literature in criminology, law and political science, in order to critically review the relationship between the developing body of human rights theory and practice, and the criminal justice system. This book will be of considerable interest to those with academic concerns in this area; as well as providing an accessible, yet sophisticated, resource for upper level undergraduate and postgraduate human rights courses'--
Human rights and contemporary criminology -- European convention on human rights and contemporary human rights thinking -- Human rights in British and European law -- Recent court cases and their principles -- Race and gender issues and human rights -- Victims, victimology and human rights -- Terrorism: terror and its implications for human rights -- The problems of a globalised world: transnational justice issues -- The rights of prisoners -- Conclusion.
' A Glasshouse book'
Includes bibliographical references and index.
Keywords: Human rights; Criminal justice, Administration of